Oleaginosas amazônicas usadas na produção de biodiesel - Aguiar, Diana da Costa (Brasil, 2021)
Biodiesel is a real alternative to replace fossil diesel oil derived from oil, it is produced from renewable sources such as vegetable oils, fats animals and even residual oils from frying. Brazil, for having a large extension territorial, presents a wide diversity of raw materials for the production of biodiesel, such as soy, sunflower, castor bean, corn, jatropha, cottonseed, canola, babassu, buriti, palm oil, macaúba and peanuts. Raw materials and processes of production depend on the region considered. In the Amazon region, other species such as andiroba, inajá, Brazil nuts and tucumã have potential for the production of biodiesel, some of which already have a consolidated market in the region for food and cosmetic purposes. The present work has as main objective carry out a bibliographical review on the Amazonian oilseeds, tucumã, palm oil, babassu and inajá. In the methodology, a narrative review of the literature was carried out, which has as a basis only some works or sources on the subject that are considered more important and are able to provide current and relevant data on the subject. Accordingly with the works analyzed among these species, the babassu presented a higher cost in production when compared to the production of biodiesel made from another raw material. O palm oil stood out with productivity that can be over 5,000 kg of oil/ hectare/year, when compared to other oilseeds, in addition to having a lower cost of production. Regarding inajá, further studies of the physical and chemical properties are needed to qualify the biodiesel produced from almonds. Tucumã stood out as the oilseed with potential for biodiesel production due to its high lipid content, however, it needs a plan for the sustainable use of this species.